2019
DOI: 10.1371/journal.pntd.0007101
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the association between being seropositive for cysticercosis and the prevalence of epilepsy and severe chronic headaches in 60 villages of rural Burkina Faso

Abstract: BackgroundIndividuals diagnosed with neurocysticercosis often present with epilepsy and sometimes with progressively worsening severe chronic headaches (WSCH). While cross-sectional associations between seropositivity to cysticercal antigens and epilepsy have been reported, few large scale studies have been conducted in West Africa and none have measured the association between seropositivity to cysticercal antigens and headaches. This study aimed at filling these knowledge gaps by estimating the strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Also, the high frequency of antigen positivity in patients with neurological disorders is compatible with the hypothesis that this infection plays some causal role [4,31]. It is worth reminding in addition that neurocysticercosis tends to become clinically apparent when the cystic lesions degenerate, through local in ammatory reactions, while active cysts alone usually cause little neurological symptoms [32].…”
Section: Discussionsupporting
confidence: 60%
“…Also, the high frequency of antigen positivity in patients with neurological disorders is compatible with the hypothesis that this infection plays some causal role [4,31]. It is worth reminding in addition that neurocysticercosis tends to become clinically apparent when the cystic lesions degenerate, through local in ammatory reactions, while active cysts alone usually cause little neurological symptoms [32].…”
Section: Discussionsupporting
confidence: 60%
“…Additional studies performed later on in Africa revealed that the proportion of neurocysticercosis in patients with epilepsy varied a lot according to the setting and could range from 15-50% [24,[28][29][30]. in patients with neurological disorders is compatible with the hypothesis that this infection plays some causal role [4,31]. It is worth reminding in addition that neurocysticercosis tends to become clinically apparent when the cystic lesions degenerate, through local inflammatory reactions, while active cysts alone usually cause little neurological symptoms [32].…”
Section: Discussionmentioning
confidence: 71%
“…• true prevalence of T. solium infection in humans and pigs because of poor diagnostic methods • adult tapeworm life span • effect of pig-to-people population ratio on transmission • processes regulating parasite acquisition in humans and pigs 26 • health and economic burden 2,3 and cost-effectiveness of interventions (DALYs likely to underestimate disease burden); possible use of the zoonotic zDALY metric 21 • linking infection to disease models, particularly to human neurocysticercosis and epilepsy 27 What are the biggest risks?…”
Section: Collaboration To Improve Modellingmentioning
confidence: 99%